Discussing the Reality Gap by Comparing Physics Engines in Kilobot Simulations - Andreas Meier; Sascha Carroccio; Rolf Dornberger; Thomas Hanne (Universitas Muhammadiyah Yogyakarta, 2021)
The difference between real experiments and their simulated counterparts, the so-called reality gap, is dependent on various factors and a challenging issue for every simulation-based robot experiment. The reality gap in robot experiments is often caused by software, which is not always able to sufficiently capture particular details and process them properly. In order to minimize this difference, this paper strives to assess different simulation physics engines in V-REP, the simulation framework for the Kilobot swarm robots. The outcome of the simulation software adaption is based on a unified multi robot experiment applied to Kilobots. This paper proposes a simulation attitude, which reflects the outcomes of a real world experiment with Kilobots accurately.